PENDAMPINGAN PERPAJAKAN PADA USAHA MIKRO, KECIL, DAN MENENGAH DI KABUPATEN KUDUS - Nita Andriyani Budiman; Sri Mulyani (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
In 2017, the MSME sector in Indonesia has a role of 60.34% of GDP formation. However, the magnitude of the contribution of MSMEs is not accompanied by its contribution to tax revenues. The PKM target audience is MSMEs in Kudus Regency. There are still many conditions for MSMEs in Kudus Regency who do not yet have an understanding of taxes, do not know about the implementation of PP No. 23 of 2018 concerning MSME tax, do not understand the importance of financial records, calculate the amount of tax and do not know how to make a tax report. The solution offered in this PKM is to provide information about PP No. 23 of 2018 and provide assistance on financial records, calculations and tax reporting for MSMEs. The purpose of this PKM activity is 1) to provide understanding and knowledge to MSME actors in Kudus Regency about taxation, 2) to provide awareness about the importance of taxes for MSMEs, 3) to increase understanding for MSME actors regarding PP No. 23 of 2018, and 4) provide an understanding of the process of recording finance, calculating the amount of tax to be paid and making tax reporting. The problems in this PKM will be solved by stages of activities, namely: training, discussion and practice.